Beginning the walk : 18 sessions on Jesus the way, the truth, and the life - Bennett, Mary (Pastor) (NavPress, 2018)
Following Jesus' Start Here. Following Jesus isn't always clear cut. Fortunately, many people have walked the path ahead of us, and we can learn a lot from them. Learn what you'll need from some of Jesus' earliest followers in this 18-lesson Bible study. Paul, John, and others will make sure you're ready for the journey. Beginning the Walk provides you the essentials you'll need along the way, including your identity in Christ, faith, the Word, prayer, community, grace, and the Holy Spirit's guidance. There's no need to feel lost. Find the resources you need and stay focused on Christ'every step of the way.